2018
DOI: 10.1088/1361-6439/aaaf2f
|View full text |Cite
|
Sign up to set email alerts
|

High-aspect-ratio microstructures with versatile slanting angles on silicon by uniform metal-assisted chemical etching

Abstract: High-aspect-ratio (HAR) microstructures on silicon (Si) play key roles in photonics and electromechanical devices. However, it has been challenging to fabricate HAR microstructures with slanting profiles. Here we report successful fabrication of uniform HAR microstructures with controllable slanting angles on (1 0 0)-Si by slanted uniform metal-assisted chemical etching (SUMaCE). The trenches have width of 2 µm, aspect ratio greater than 20:1 and high geometric uniformity. The slanting angles can be adjusted b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Because of the small critical dimension, the step-like profile and hollow structures are almost unnoticeable, giving a smooth wigging structure profile. It should be noticed that metal-assisted chemical etching can also be used to create tilted or even zigzag-like silicon structures [22,23], while to create wiggling silicon structures with plasma etching techniques has not been reported before. By making use of the fluorocarbon/silicon-based hollow structures (and possibly an additional process of fluorocarbon film deposition to enclose the microcavities), it can be promising to fabricate microcontainers or reservoirs for biological or medical applications [24,25].…”
Section: Resultsmentioning
confidence: 99%
“…Because of the small critical dimension, the step-like profile and hollow structures are almost unnoticeable, giving a smooth wigging structure profile. It should be noticed that metal-assisted chemical etching can also be used to create tilted or even zigzag-like silicon structures [22,23], while to create wiggling silicon structures with plasma etching techniques has not been reported before. By making use of the fluorocarbon/silicon-based hollow structures (and possibly an additional process of fluorocarbon film deposition to enclose the microcavities), it can be promising to fabricate microcontainers or reservoirs for biological or medical applications [24,25].…”
Section: Resultsmentioning
confidence: 99%
“…During etching, as illustrated in Figure 1a, obliquely incident etching particles can preferentially remove the tops of "hills" due to their higher heights, while lower lying "valleys" get shadowed and stay intact. Therefore, shadowing has a smoothening effect during the etching process as opposed to its roughening effect in deposition and dominates over the roughening effect of noise, leading to very smooth surfaces [7,11,12]. However, it has been shown that [13] etched surfaces can remarkably get rougher due to the competition between shadowing and "re-emission effects."…”
Section: Introductionmentioning
confidence: 99%